Optimum Population Size of Indigenous P-solubilizing Bacteria to Correct P Availability in Acid Soils - . Sabaruddin; . Marsi; . Desti (UNIVERSITY OF LAMPUNG, 2011)
Indonesian acid soils were used to determine an optimum population size of indigenous P-solubilizing bacteria (PSB) for solubilizating fixed P. The experiment consisted of two sub-experiments. Sub-experiment I was to isolate the indigenous PSB from Ultisols, Fresh-water lowland Inceptisols, and tidal-swamp Inceptisols. Subexpriment II was to study the capacity of the isolated PSB to correct P availability in acid soils by inoculating the isolated PSB into the tested soils at 0, 105, 1010, and 1015 cells. The population of the indigenous PSB in the tested soils increased as a result of the inoculation. Both Al-P and Fe-P content in the three tested soils decreased as compared with the initial content. The increases of available P were significantly correlated with the decreases both in Al-P (r2 = 0.68 for the Ultisols; r2 = 0.51 for the fresh-water Inceptisols; and r2 = 0.35 for the tidal-swamp Inceptisols) and in Fe-P (r2 = 0.91 for the Ultisols; r2 = 0.45 for the fresh-water lowland Inceptisols; and r2 = 0.78 for the tidal-swamp Inceptisols). The increases of available P were significantly correlated with the increases of thepopulation of the PSB (r2 = 0.60 for the Ultisols; r2 = 0.55 for the fresh-water lowland Inceptisols; and r2 = 0.69 for the tidal-swamp Inceptisols). The available P in the three tested soils sharply increased if the population size of the PSB was about 1 × 109 cfu g-1 of soil.Keywords: Al-P, Fe-P, fresh-water lowland, isolated, Pikovskaya medium, tidal swamp